Library as Showcase: Reflections on a Roundtable Discussion - Wills, Deborah (CAML Review / Revue de l'ACBM, 2015)
Based on a roundtable discussion at ACRL 2015, this article explores the benefits and challenges of showcasing and celebrating the creative output of our communities. Such ventures serve the dual purpose of highlighting the contributions of our students, faculty, staff and alumni, while establishing the library as a centre for collaboration and cultural enrichment.